![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
a: Ta có: \(142-\left[50-\left(2^3\cdot10-2^3\cdot5\right)\right]\)
\(=142-\left[50-80+40\right]\)
=142-10
=132
a. 142 - [50-(23.10-23.5)]
= 142 - [ 50 - ( 8 . 10 - 8 . 5 )]
= 142 - [ 50 - ( 80 - 40 )]
= 142 - [ 50 - 40 ]
= 142 - 10 = 132
b. 375 : { 32[ 4+(5.32 - 42 )]} - 14
= 375 : { 32[4+(5.9 - 42 )]} - 14
= 375 : { 32[4 + ( 45 - 42 )]} - 14
= 375 : {32[4+3]} - 14
= 375 : 224 - 14
c.{210 : [ 16+3.(6+3.2^2)]} - 3
= {210 : [ 16 + 3.(6+3.4)]} - 3
= { 210 :[16+3.(6+12)]}-3
= {210 : [ 16+3.18)]} - 3
= { 210 : [ 16 + 54]} - 3
= { 210 : 70 } - 3
= 30 - 3 = 27
d.500-{5.[409-(2^3 . 3-21^2)] - 1724}
= 500-{5.[409-(8 . 63 - 21^2] - 1724}
= 500 - { 5.[409- (504 - 441) - 1724}
= 500 -{ 5.[ 409 - 63 ] - 1724}
= 500 - { 5.346 - 1724}
= 500 - { 1720 - 1724 }
= 500 - 6
= 494
![](https://rs.olm.vn/images/avt/0.png?1311)
a,da thuc nay ko phan tich duoc
b,x2 +9x -10 c,5x2 -3x +2
= x2 - x +10 -10 = 5x2 -5x +2x +2
= x (x-1) +10(x -1) = 5x (x-1 )+2(x+1)
= (x-1)(x+10) = 5x (x-1) -2(x-1)
= (x-1)(5x-2)
d,x2 -13x +42= x2 -7x-6x +42
= x(x-7) -6(x-7)
=(x-7)(x-6)
![](https://rs.olm.vn/images/avt/0.png?1311)
Ta có :
6x = 3x+1-5x+6x-5x+4x-9x+7x
=> 6x+1 = (3x+7x) - (5x+5x) + (6x+4x) - 9x
=> 6x+9x+1 = 10x - 10x + 10x
=> 15x+1 = 10x
=> 10x-15x = 1
=> -5x = 1
=> x = 1 : (-5)
=> x = -1
Vậy x = -1
![](https://rs.olm.vn/images/avt/0.png?1311)
a)4.(x+3)-(2x-12)=x-(-11+4)
4x+12-2x+12=x+11-4
2x+24=x+7
2x-x=-24+7
x=-17
b)-(4x-13)+(5x-4)=-3-(-15+7)
-4x+13+5x-4=-3+15-7
(-4x+5x)+13-4=12-7
x+9=5
x=-4
c)(5x-3)-(-2x+4)=6x-12
5x-3+2x-4=6x-12
5x+2x-6x=3+4-12
x=-5
d)(15x+20)-(9x-3)=5x-(-12)
15x+20-9x+3=5x+12
15x-9x-5x=-20-3+12
x=-11
e,(7x+14)+(3x-8)=-(-9x+3)
7x+14+3x-8=9x-3
7x+3x-9x=-14+8-3
x=-9
![](https://rs.olm.vn/images/avt/0.png?1311)
3\(x^2\).(5\(x\) + 1) + 6\(x^3\).(5\(x\) + 2) = 9\(x^3\) .(5\(x\) + 3)
15\(x^3\) + 3\(x^2\) + 30\(x^4\) + 12\(x^3\) = 45\(x^4\) + 27\(x^3\)
(15\(x^3\) + 12\(x^3\)) + 3\(x^2\) + 30\(x^4\) - 45\(x^4\) - 27\(x^3\) = 0
27\(x^3\) + 3\(x^2\) - 15\(x^4\) - 27\(x^3\) = 0
3\(x^2\) - 15\(x^4\) = 0
3\(x^2\).(1 - 5\(x^2\)) = 0
\(\left[{}\begin{matrix}x^2=0\\1-5x^2=0\end{matrix}\right.\)
\(\left[{}\begin{matrix}x=0\\5x^2=1\end{matrix}\right.\)
\(\left[{}\begin{matrix}x=0\\x=\mp\dfrac{\sqrt{5}}{5}\end{matrix}\right.\)
x = -23 nhé
\(9x+42=5x-50\)
\(4x=-92\)
\(x=-23\)